2019
DOI: 10.1371/journal.pone.0213599
|View full text |Cite
|
Sign up to set email alerts
|

‘It was nothing that you would think was anything’: Qualitative analysis of appraisal and help seeking preceding brain cancer diagnosis

Abstract: BackgroundThe patient’s interpretation of the events and decisions leading up to consultation with a healthcare professional for symptoms of brain cancer is under researched. The aim of this study was to document responses to noticing the changes preceding a diagnosis of brain cancer and living with them, focusing on appraisal of changes and the decision to seek (and re-seek) help, with attention to the psychological processes underpinning the appraisal and help-seeking intervals.MethodIn this qualitative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…12 A psychological study showed that subtle changes were often misinterpreted by the patients and that a faster decision-making was rather obtained within a social context. 20 The relatively long time to diagnosis interval in brain tumors should lead to a reconsideration of certain symptoms, especially of visual disturbances. Visual disturbances especially of blurred and/or double vision might be an indicator for increased intracranial pressure and should therefore lead a more intense diagnostic workup.…”
Section: Discussionmentioning
confidence: 99%
“…12 A psychological study showed that subtle changes were often misinterpreted by the patients and that a faster decision-making was rather obtained within a social context. 20 The relatively long time to diagnosis interval in brain tumors should lead to a reconsideration of certain symptoms, especially of visual disturbances. Visual disturbances especially of blurred and/or double vision might be an indicator for increased intracranial pressure and should therefore lead a more intense diagnostic workup.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, is this because these heuristics are less useful to the interpretation of the studied potential cancer symptoms, or because they are less well articulated? Recent work on changes preceding diagnosis of a brain tumour indicates that attribution to stress is a common response to noticing changes in sleep, mood, and cognitive function …”
Section: Discussionmentioning
confidence: 99%
“…The symptoms that patients experienced before a brain tumour diagnosis and how these were reported and responded to in primary care are presented in this article. The psychological approaches underpinning the appraisal and help-seeking processes, often over several consultations, are reported elsewhere 28…”
Section: Methodsmentioning
confidence: 99%
“…The psychological approaches underpinning the appraisal and help-seeking processes, often over several consultations, are reported elsewhere. 28 …”
Section: Methodsmentioning
confidence: 99%